Reformulasi Metode Penafsiran Al-Qur'an Melalui Metode Tajdidi - Ainur Rhain; Andri Nirwana AN; Bahar Agus Setiawan (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Reformulation of Al-Qur'an Interpretation Method Through Tajdidi MethodTafsir at-Tanwir is the official institutional interpretation of Muhammadiyah Organization on the Qur’an. This research aims at exploring the reformation brought by at-Tanwir which include the new methods in interpreting of The Quran. What is the latest method offered by at-Tanwir. This research is categorized as a library research, focusing on written sources, such as books, journals and magazines published by the Council. Qualitative analysis and deductive method have been emlpoyed to analyze the data.This research discusses the latest method of interpretation presented by Tafsir at-Tanwir. At-Tanwir presents a new method in the interpretation of the Qoran called tajdidi method. The tajdidi method is a method of interpreting the Qoran which is written in tahlili or sequentially from al-Fatihah to an-Nas, but the discussion is grouped into separate themes (maudhui') in several equivalent verses (munasabah). At-Tanwir succeeded in combining the tahlili and thematic (maudhu'i) methods in an interpretation called the tajdidi method, or the renewal method, which is a combined method of tahlil and thematic (maudhu'i), namely the interpretation of the Qur'an by tahlili but divided into several related themes